PARTIAL TRISOMY CHROMOSOME 5 COSEGREGATING WITH SCHIZOPHRENIA - Bassett, Anne S. (1988)
Schizophrenia was associated with a distinct autosomal abnormality in two related mildly dysmorphic individuals. The finding of cosegregation of schizophrenia and a partial trisomy of chromosome 5 in the family suggests a potential location of a gene or genes linked to schizophrenia.